INNOVATIVE LEARNING SYSTEM DESIGN: EFFECTIVE STRATEGY DESIGN AND UTILISATION OF LEARNING RESOURCES TO IMPROVE EDUCATION QUALITY FROM A LITERATURE REVIEW PERSPECTIVE - Rosdiana Mata; Suhari Suhari (INJOSEDU: International Journal of Social and Education, 2025)
This study aims to analyse the concepts and practices of innovative learning system design through a literature review of various publications discussing effective strategies and the utilisation of learning resources to improve the quality of education. In facing the challenges of the 21st-century education revolution, learning systems are required to be more adaptive, collaborative, and oriented towards developing the competencies of learners. This study emphasises that the design of innovative learning strategies is not only related to the use of technology, but also includes a transformation of the pedagogical paradigm that places learners at the centre of the learning process. Effective learning strategies involve active interaction, project-based approaches, and the application of instructional design models such as ADDIE and TPACK that integrate pedagogical aspects with technology. Furthermore, the results of the literature review show that the use of learning resources — both conventional and digital — plays a significant role in creating meaningful and inclusive learning. The integration of digital learning resources, the use of Open Educational Resources (OER), and the development of students' digital literacy strengthen access to and equitable quality of education. In this context, the collaboration between learning strategies and learning resources is an important foundation in building an education ecosystem that is oriented towards competence, creativity, and sustainability. This study concludes that the success of an innovative learning system depends on the ability of educators to design adaptive strategies and manage learning resources effectively according to the needs of learners and institutional conditions.